Molecular Mechanisms and Therapeutic Perspectives of Gut Microbiota, Autophagy, and Apoptosis in Cholangiocarcinoma Pathophysiology - RUIZ POZO, VIVIANA ALEJANDRA; CADENA ULLAURI, SANTIAGO ANDRÉ; GUEVARA RAMÍREZ, ALEXANDRA PATRICIA; TAMAYO TRUJILLO, VICTOR RAFAEL; PAZ CRUZ, ELIUS ANDRES; Cabrera-andrade Alejandro; ZAMBRANO ESPINOSA, ANA KARINA (MDPI AG, 2025)
Cholangiocarcinoma (CCA) is an aggressive malignancy of the biliary tract with rising global incidence and limited treatment options. Its pathogenesis involves a complex interplay of genetic mutations, epigenetic dysregulation, inflammatory signaling, and environmental influences. Emerging evidence highlights the pivotal role of the gut–liver axis and microbiota dysbiosis in shaping biliary homeostasis and disease progression. Alterations in microbial composition disrupt apoptosis and autophagy, two key processes regulating cell survival and death, thereby contributing to tumorigenesis, metastasis, and therapy resistance. Specific taxa, including Enterococcus, Escherichia coli, Pseudomonas, Bifidobacterium, and Bacillus, demonstrate strain-dependent effects, acting either as tumor promoters through genotoxic metabolites and immune evasion or as potential tumor suppressors by inducing apoptosis and immune activation. These findings underscore the context-dependent roles of microbiota in CCA biology. Importantly, microbiota modulation offers novel therapeutic opportunities. Dietary interventions such as probiotics, prebiotics, and nutritional strategies, alongside innovative microbiome-targeted therapies, hold promise for restoring microbial balance, enhancing antitumor immunity, and improving patient outcomes. This review integrates current molecular and microbiological evidence to propose the gut microbiota as both a biomarker and a therapeutic target in CCA, opening avenues for precision medicine approaches in hepatobiliary oncology